Nutrition Mass Changes of Teak Leaves (Tektona grandis) Complete Feed Silage Fermented at Different Storage Duration - S. Santi; Andi Fausiah (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
This study aimed to increase the nutritional value of teak leaves as feed for ruminants by carrying out fermentation at different storage times. This research was conducted in April - July 2020. The preparation of complete feed silage made from teak leaves (Tektona grandis)was carried out in the UNASMAN Animal Husbandry Study Program. The nutritional analysis was carried out at the Feed Chemistry Lab, Faculty of Animal Husbandry, Hasanuddin University. This study was designed using the CRD method with five treatments and three replications so that the number of experimental units was 5. The treatments are A0 = 0 weeks (control); A1 = 2 weeks; A2 = 4 weeks; A3 = 6 weeks; A4 = 8 weeks. The results showed that storage time had a significant effect lower (P 0.05) on the nutrients mass (dry matter, crude protein, crude fat, and crude fiber). Storage of complete feed silage made from teak leaves is effective for 2-4 weeks of storage.